The Efficacy of 3D Imaging and Cone-Beam Computed Tomography (CBCT) in Enhancing Endodontic Diagnosis and Treatment Planning (International Journal of Scientific Research and Management (IJSRM), 2018)
Endodontic diagnosis and treatment planning rely heavily on imaging techniques to accurately assess root canal morphology, periapical pathologies, and anatomical variations. Traditional 2D radiographic methods, such as periapical and panoramic radiographs, have been widely used but are limited by image distortion, anatomical superimposition, and reduced sensitivity in detecting small periapical lesions and complex root canal configurations. In contrast, Cone-Beam Computed Tomography (CBCT) has emerged as a highly effective three-dimensional (3D) imaging modality, offering superior diagnostic accuracy and treatment precision in endodontics. This study explores the efficacy of CBCT in enhancing endodontic diagnosis and treatment planning by evaluating its advantages, clinical applications, and comparative accuracy with conventional radiography. A systematic review of recent peer-reviewed literature and clinical studies was conducted to assess CBCT’s role in detecting periapical lesions, vertical root fractures, root canal variations, and root resorption. Statistical comparisons reveal that CBCT has a sensitivity of 89% and specificity of 91% in detecting periapical lesions, significantly higher than conventional radiography, which exhibits a sensitivity of 64% and specificity of 70%. Additionally, CBCT has been shown to identify complex root canal systems with 87% accuracy, compared to 54% with periapical radiography. Furthermore, this paper discusses the advantages of CBCT, including high-resolution imaging, multiplanar reconstructions, and elimination of anatomical superimposition, which contribute to more accurate diagnoses and improved treatment outcomes. Despite these benefits, the study also examines limitations such as higher radiation exposure, increased cost, and the presence of image artifacts that may affect widespread adoption in general dental practice. The findings emphasize the critical role of CBCT in complex endodontic cases, retreatments, and guided endodontic microsurgery, where precise anatomical assessment is essential. The integration of AI-driven CBCT analysis and low-dose CBCT technology is expected to further enhance diagnostic accuracy while minimizing patient radiation exposure. In conclusion, while CBCT should not be used as a routine imaging tool for all endodontic cases, its selective and justified use in challenging cases significantly enhances diagnostic precision and treatment planning, ultimately improving patient outcomes.